A Timetabling Application for the Assignment of School Classrooms - Marmolejo Saucedo, José Antonio; Rodríguez Aguilar, Román (My University, 2019)
In this manuscript a group of students from an university of Mexico develop a user-friendly university timetabling tool based on a spreadsheet and using Open-Solve optimization software. The developed tool uses 0–1 integer programming to maximize the number of classes with their respective teacher allocated to a classroom in a certain time schedule. It does not solve only one specific case, the user can introduce each semester’s specific information to the spreadsheet and the tool will automatically generate a schedule that maximizes the number of classes assigned using the given time and classroom resources. Each semester the available times and the teacher can be changed for each class according to the needs for that specific semester. The user does not need to be someone who understands linear programming. The tool is developed on a user-friendly way so that the staff of the school can use it without help from the developers. In this paper we will show how this tool was developed for a smaller example and how it works with a real case. © 2020, Springer Nature Switzerland AG.
Keywords: Assignment problems; Mixed-integer programming; Timetabling; Combinatorial optimization; Intelligent computing; Linear programming; Scheduling; Spreadsheets; Mixed integer programming; Number of class